An integrative multi-omics approach reveals metabolic mechanism of flavonoids during anaerobic fermentation of de'ang pickled tea - Honglin Mao; Yang Xu; Fengmei Lu; Cunqiang Ma; Shaoxian Zhu; Guoyou Li; Siqi Huang; Yi Zhang; Yan Hou (Food Chemistry: X)
Anaerobic fermentation (AF) is critical process for Yunnan De'ang pickled tea production. Therefore, widely targeted metabolomics and metagenomics were integrated to reveal the AF mechanism. Lactic acid bacteria (LAB) (e.g. Lactiplantibacillus plantarum, Lactobacillus vaccinostercus and Lactobacillus paracollinoides) and yeasts like Candida metapsilosis and Cyberlindnera fabianii dominated in the AF. Based on bacterial community succession and metabolites variation, the whole AF processes were divided into two phases, i.e., before and after four months. A total of 327 characteristic metabolites (VIP >1.0, P < 0.05, and FC > 1.50 or < 0.67) were selected from the AF. Besides amino acids increase, LAB and yeasts also promoted non-galloylated catechins, and several simple flavones/flavonols, flavanones/flavanonols and methoxy flavones/flavonols accumulations along with galloylated catechins, flavonol/flavone glycosides and anthocyanins decrease during the AF. This study would improve the understanding about AF mechanism of tea-leaves from the perspectives of flavonoids metabolism and microbial community succession.